2013
DOI: 10.1103/physrevlett.111.100501
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Information from a Qubit by Multiple Observers: Toward a Theory of Sequential State Discrimination

Abstract: We discuss sequential unambiguous state-discrimination measurements performed on the same qubit. Alice prepares a qubit in one of two possible states. The qubit is first sent to Bob, who measures it, and then on to Charlie, who also measures it. The object in both cases is to determine which state Alice sent. In an unambiguous state discrimination measurement, we never make a mistake, i.e., misidentify the state, but the measurement may fail, in which case we gain no information about which state was sent. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
151
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(156 citation statements)
references
References 14 publications
4
151
1
Order By: Relevance
“…One also can obtain these results by calculating the limits of (15) and (17). In the limit of θ 0 = θ 1 → 0,…”
Section: Lf Xu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…One also can obtain these results by calculating the limits of (15) and (17). In the limit of θ 0 = θ 1 → 0,…”
Section: Lf Xu Et Almentioning
confidence: 99%
“…Since the solution of |η i for the absence of entanglement in state ρ SA is not unique, we choose the ones satisfying the equations (17)(18)(19)(20), which provides a uniform treatment to the four cases of priori probabilities and overlap. Since the GMQD is not normalized to one and its value for maximally entangled qutrit-qubit states is 0.5, we plot the quantity 2D G (ρ SA ) for the case with equal a priori overlaps in Fig.…”
Section: Lf Xu Et Almentioning
confidence: 99%
“…The problem studied here is closely related to that of sequential measurements on the same quantum system [6][7][8]. Rather surprisingly, it has been shown that one can gain information about the initial state of a system even though a measurement has intervened and changed the state of the system [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum entanglement and hyperentanglement are highly important, fundamental, and indefeasible features of quantum mechanics. Entangled states have numerous applications in emerging technologies such as quantum computing [1], quantum cryptography [2,3], quantum teleportation [4][5][6], and quantum algorithms [7,8]. The highly attractive hyperentangled states extend possibilities of quantum technologies, allowing new quantum communication protocols, superdense teleportation [10], and objects with higher dimensionality [9].…”
mentioning
confidence: 99%
“…The considered system should be realizable on a single chip using current waveguide technology in the LiN bO3 platform. [4][5][6], and quantum algorithms [7,8]. The highly attractive hyperentangled states extend possibilities of quantum technologies, allowing new quantum communication protocols, superdense teleportation [10], and objects with higher dimensionality [9].…”
mentioning
confidence: 99%